MeiNews: uma solução jornalística para o fortalecimento do microempreendedorismo Individual em Uberlândia - Angerami, Thaís Degani (2024)
Entrepreneurship has become a reality in Brazil. The Covid-19 pandemic brought a wave of layoffs and with unemployment rising, the solution for many was to try to open their own business. The so-called entrepreneurship out of necessity. These people were forced to enter into an activity that was often unknown, to guarantee income. These are individual microentrepreneurs. And even after the pandemic, the sector has been growing. The number of entrepreneurs is only increasing in the country and in the city of Uberlândia is no different. And how can they overcome the effects of the pandemic period on the economy? How can they strengthen their business against a consolidated market? How to compete with the competition and guarantee their livelihood? How to increase income by increasing sales? To answer these questions and help micro-entrepreneurs, this project proposes a journalistic product that can fulfill this role: the creation of a newsletter that, through content curation, provides useful and applicable information, contributing to the strengthening of small businesses in Uberlandia. The method applied for the creation of the product was design thinking (Brown, 2017) as a form of brainstorming, followed by the application of a market research form to better define the product, and the realization of a pilot project of a newsletter with microentrepreneurship consultants in the region. It is believed that this product with its application plan can contribute to the MEI category in the Uberlândia region, in the sense of bringing sources of experts and consultants, bringing the main news about this universe and also information on the local agenda, strengthening the sector in the region.